2001
DOI: 10.1016/s0960-9822(01)00225-1
|View full text |Cite
|
Sign up to set email alerts
|

Tumor suppressor and anti-inflammatory actions of PPARγ agonists are mediated via upregulation of PTEN

Abstract: The PTEN tumor suppressor gene modulates several cellular functions, including cell migration, survival, and proliferation [1] by antagonizing phosphatidylinositol 3-kinase (PI 3-kinase)-mediated signaling cascades. Mechanisms by which the expression of PTEN is regulated are, however, unclear. The ligand-activated nuclear receptor peroxisome proliferator-activated receptor gamma (PPARgamma) [2] has been shown to regulate differentiation and/or cell growth in a number of cell types [3, 4, 5], which has led to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
246
2
6

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 341 publications
(275 citation statements)
references
References 21 publications
21
246
2
6
Order By: Relevance
“…36 Prior studies, which tested Rosi's ability to induce PTEN in MCF-7 cells, studied its effect at only 1 dose, 1 lM. 18 Studying Rosi's effects on PTEN at 1 dose limits one's ability to detect a potentially more significant dose effect. We, therefore, determined the optimal concentration for increased PTEN expression, by studying our agonists in a dose curve.…”
Section: Lovastatin and Rosiglitazone (Rosi) Induce Pten Protein Exprmentioning
confidence: 99%
See 2 more Smart Citations
“…36 Prior studies, which tested Rosi's ability to induce PTEN in MCF-7 cells, studied its effect at only 1 dose, 1 lM. 18 Studying Rosi's effects on PTEN at 1 dose limits one's ability to detect a potentially more significant dose effect. We, therefore, determined the optimal concentration for increased PTEN expression, by studying our agonists in a dose curve.…”
Section: Lovastatin and Rosiglitazone (Rosi) Induce Pten Protein Exprmentioning
confidence: 99%
“…17 In 2001, 2 putative binding sites for the transcription factor peroxisome proliferator-activated receptor-gamma (PPARg) were identified about 10 kb upstream of the minimal promoter region of PTEN. 18 However, the biological importance of these sites and what role PPARg plays in PTEN transcription has not been determined. Therefore it remains to be determined if PPARg has a role in PTEN transcription, and if so, which regions of the PTEN promoter are responsible.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that the expression and enzymatic DOI:http://dx.doi.org/10.7314/APJCP.2014.15.1.17 Roles of PTEN (Phosphatase and Tensin Homolog) in Gastric Cancer activity of PTEN can be regulated at transcriptional, microRNA (miRNA), and post-translational levels. Positive regulators of PTEN gene expression include, EGR1 (early growth response protein 1), PPARγ (peroxisome proliferator-activated receptor γ) and Tp53 (tumor protein 53; also known as p53); these were shown to directly bind to the PTEN promoter region (Patel et al, 2001;Stambolic et al, 2001;Virolle et al, 2001;Martelli et al, 2011). Negative regulators include MKK-4 (mitogen activated protein kinase kinase-4), TGF-β (transforming growth factor beta), NFκB (nuclear factor of kappa light polypeptide gene enhancer in B-cells), transcriptional cofactor c-JUN and oncogene BMI1; these were shown to suppress PTEN expression in several cancer models (Gericke et al, 2006;Lau et al, 2011;Meng et al, 2012).…”
Section: Regulation Of Pten Expressionmentioning
confidence: 99%
“…Thus the activated PPARγ exerts an anti-proliferative effect 20) and increases pro-apoptotic effect by positively regulation of Fas ligand expression 21) . Moreover, PPARγ activation by 15d-PGJ 2 inhibits the activities of the transcriptional factors AP-1, STAT and NFκB 22) , and at least three important genes including the VEGF receptors 1 (Flt-1), 2 (Flk/KDR) and the urokinase plasminogen activator (uPA) during the angiogenic process 23) .…”
mentioning
confidence: 99%